PENYULUHAN LITERASI DIGITAL SEBAGAI PEMANFAATAN MEDIA DIKALANGAN MASYARAKAT DI RW 05 KELURAHAN CIMONE KOTA TANGERANG - Latuconsina, Hudaya; Lesmana, Sri Jaya; Djamaludin, Djamaludin; Fahmi, Rizal (Nindikayla Institute, 2023)
Digital literacy has become an essential skill in today's digital age. Knowledge and ability to use digital media is a valuable asset for the community, revealing the importance of digital literacy counseling as a tool to utilize digital media among the community. The results of the analysis show that many people are still not familiar with digital literacy and its benefits. Digital literacy counseling can help them understand the risks and benefits of using digital media. Students of the UNIS Tangerang Community Work Lecture (KKK) work together with the local community to increase understanding of digital literacy. This counseling helps the people of Cimone Village in Tangerang City to understand the benefits of using digital media in their daily lives, including education, information, and communication. Through collaboration between KKK students and the community, this program has succeeded in building awareness about the importance of digital literacy and the use of digital media. In addition, this counseling also creates an environment that supports the development of digital skills of the people of Cimone Village, so that they can be more active and effective in accessing information and resources in the digital era.